PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN FUN THINKERS BOOK TERHADAP HASIL BELAJAR IPAS MURID KELAS IV DI SD NEGERI ANUSU KECAMATAN TAPALANG KABUPATEN MAMUJU - Pada, Amir; Atika Dani; Sayidiman, Sayidiman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine: (1) the use of Fun Thinkers Book learning media in the content of science subjects for fourth-grade students at Anusu State Elementary School, Tapalang District, Mamuju Regency; (2) the results of learning science subjects of fourth-grade students at Anusu State Elementary School, Tapalang District, Mamuju Regency before and after using Fun Thinkers Book media; and (3) the effect of using Fun Thinkers Book media on the results of learning science subjects of fourth-grade students at Anusu State Elementary School, Tapalang District, Mamuju Regency. This study used a quasi-experimental method with a nonequivalent control group design. Data analysis techniques included descriptive statistics and inferential statistics with the help of the IBM SPSS program version 26. The results of the study showed that: (1) the use of Fun Thinkers Book media in science subjects learning was in the very good category; (2) student learning outcomes increased significantly, from the sufficient category before treatment to very high after treatment; and (3) the use of Fun Thinkers Book had a significant effect on improving the results of learning science subjects of fourth-grade students.